The Brain Alteration of Seafarer Revealed by Activated Functional Connectivity Mode in fMRI Data Analysis - Shi, Yuhu; Zeng, Weiming; Wang, Nizhuan (Frontiers in Human Neuroscience, 2021)
As a special occupational group, the working and living environments faced by seafarers is greatly different from those of land. It is easy to affect the psychological and physiological activities of seafarers, which inevitably lead to changes in the brain functional activities of seafarers. Therefore, it is of great significance to study the neural activity rules of seafarers' brain. In view of this, this paper studied the seafarers' brain alteration at the activated voxel level based on functional magnetic resonance imaging technology by comparing the functional connectivities (FCs) difference between seafarers and non-seafarers. Firstly, the activated voxels of each group subjects were obtained by independence component analysis, and then the distribution of these voxels in the brain as well as the common activated voxels between the two groups were statistically analyzed. Next, the FCs between the common activated voxels of the two groups subjects were calculated, and obtained the FCs which had significant differences between them through two-sample T-test. Finally, all FCs and FCs with significant differences (DFCs) between the common activated voxels were used as the features for support vector machine to classify seafarers and non-seafarers. The results showed that DFCs between the activated voxels had better recognition ability for seafarers, especially for Precuneus_L and Precuneus_R, which may played an important role in the classification prediction of seafarers and non-seafarers, so that provided a new perspective for studying the specificity of neurological activities of seafarers.